Segmentation and Radial Anisotropy of the Deep Crustal Magmatic System Beneath the Cascades Arc. (3rd March 2023) - Jiang, Chengxin; Schmandt, Brandon; Abers, Geoffrey A.; Kiser, Eric; Miller, Meghan S.
Abstract: Volcanic arcs consist of many distinct vents that are ultimately fueled by the common melting processes in the subduction zone mantle wedge. Seismic imaging of crustal‐scale magmatic systems can provide insight into how melt is organized in the deep crust and eventually focused beneath distinct vents as it ascends and evolves. Here, we investigate the crustal‐scale structure beneath a section of the Cascades arc spanning four major stratovolcanoes: Mt. Hood, Mt. St. Helens (MSH), Mt. Adams (MA), and Mt. Rainier, based on ambient noise data from 234 seismographs. Simultaneous inversion of Rayleigh and Love wave dispersion constrains the isotropic shear velocity ( Vs ) and identifies radially anisotropic structures. Isotropic Vs shows two sub‐parallel low‐ Vs zones (∼3.45–3.55 km/s) at ∼15–30 km depth with one connecting Mt. Rainier to MA, and another connecting MSH to Mt. Hood, which are interpreted as deep crustal magma reservoirs containing up to ∼2.5%–6% melt, assuming near‐equilibrium melt geometry. Negative radial anisotropy, from vertical fractures like dikes, is prevalent in this part of the Cascadia, but is interrupted by positive radial anisotropy, from subhorizontal features like sills, extending vertically beneath MA and Mt. Rainier at ∼10–30 km depth and weaker and west‐dipping positive anisotropy beneath MSH. The positive anisotropy regions are adjacent to rather than co‐located with the isotropic low‐ Vs anomalies. Ascending melt that stalled and mostly crystallized in sills with possible compositional differences from the country rock may explain the near‐average Vs and positive radial anisotropy adjacent to the active deep crustal magma reservoirs. Plain Language Summary: Volcanic arcs, a common result of subduction processes, comprise a large proportion of active volcanoes in the world and pose significant hazards. Seismic tomography measures variations of seismic wave speed in the subsurface, which can then be used to infer important properties of the volcanic systems, such as the distribution and configuration of active melts in the crust. In this study, we use continuous seismic data from 234 seismography in the Cascades arc and measure the wave speed of two types of surface waves, Rayleigh and Love waves. This allows us to infer not only the averaged shear‐wave speed of the subsurface structures, but also its direction dependence, a seismic property known as seismic anisotropy. Our results show two concentrated and arc parallel low‐velocity anomalies at 15–30 km depth beneath the arc: one connecting Mt. Rainier to Mt. Adams, and another connecting Mt. St. Helens to Mt. Hood. We interpret these low‐velocity zones as deep crustal magma reservoirs with up to ∼2.5%–6% melt. We identify positive radial anisotropy adjacent to the isotropic low‐velocity anomalies at a similar depth range, and interpret them as sill complexes with mostly crystallized magma extracted from laterally offset deep crustal reservoirs. Key Points: Anisotropic Rayleigh and Love wave tomography of the Cascades arc reveals two distinct arc parallel magma reservoirs in the mid‐lower crust One connecting Mt. Rainier to Mt. Adams (MA) and another Mt. St. Helens (MSH) to Mt. Hood with ∼50 km offset at the latitudes of MA and MSH Positive anisotropy adjacent to the magma reservoirs may represent and is interpreted as sill complexes with mostly crystallized mafic magma